Efforts of Al-Istiqomah Community Reading Gardens in Increasing Children's Interest in Reading at Elementary Education Age - Suherman, Maman; Hidayat, Cece; Nuarida, Eva Bella; Qohar, Hendri Abdul (Universitas Negeri Padang, 2025)
Reading interest among primary school-aged children has become a critical issue in the field of education in Indonesia. One initiative aimed at fostering children's reading interest is through Community Reading Gardens (Taman Bacaan Masyarakat, TBM). This study seeks to explore the efforts of TBM Al-Istiqomah in enhancing children's reading interest in Cileunyi Kulon Village, Bandung Regency. The research employs a qualitative approach, conducted at TBM Al-Istiqomah, Cileunyi Kulon, Bandung Regency, from January to April 2023. Data collection techniques include observation, interviews, and documentation. Data analysis follows the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that TBM Al-Istiqomah has implemented various strategies to improve reading interest among primary school-aged children, such as providing engaging reading materials, organizing appealing and interactive literacy activities, and collaborating with PKBM institutions and other non-formal educational organizations. However, several supporting factors and challenges have been identified in these efforts, including limited funding for development, a lack of human resources, and difficulties in establishing partnerships with local government authorities